Tree growth decline to warm-wet conditions in boreal forests is linked to stand density - Bingqian Zhao; Yihong Zhu; Lushuang Gao; Qibing Zhang; Mingqian Liu; Klaus von Gadow (Forest Ecosystems)
Warm-wet climatic conditions are widely regarded as conducive to remarkable tree growth, alleviating climatic pressures. However, the notable decline in tree growth observed in the southern edge of boreal forests has heightened concerns over the spatial-temporal dynamics of forest decline. Currently, attaining a comprehensive grasp of the underlying patterns and their propelling factors remains a formidable challenge. We collected tree ring samples from a network of 50 sites across the Greater Xing'an Mountains. These samples were subsequently grouped into two distinct clusters, designated as Groups A and B. The percentage change of growth (GC, %) and the proportion of declining sites were utilized to assess forest decline. The decline in tree growth within Larix gmelinii forests exhibits significant regional variation, accompanied by temporal fluctuations even within a given region. Group A exhibited a pronounced increase in frequency (59.26%) of occurrences and encountered more severe declines (21.65%) in tree growth subsequent to the 1990s, contrasting sharply with Group B, which observed lower frequencies (20.00%) and relatively less severe declines (21.02%) prior to the 1980s. The primary impetus underlying the opposite radial growth increments observed in Larix gmelinii trees from the interplay between their differential response to temperatures and wetter climatic conditions, which is significantly influenced by varying stand densities. In cold-dry conditions, low-density forests may experience soil water freezing, exacerbating drought conditions and thereby inhibiting tree growth, in Group B. Trees growth in high-density stands is restrained by warm-wet conditions, in Group A. These results provide new insights into the variability at the southern edge of the boreal forest biome with different responses to density and climate.